Pozbawienie uprawnień wynikających z decyzji administracyjnej a realizacja zasady efektywności działania administracji - Trybka, Wiktor (Studia Prawa Publicznego, 2018)
Deprivation of an entity of acquired rights deriving from an administrative act is possible through the combined application of administrative provisions of substantive and procedural law. The limits of durability acquired under an administrative decision rights are the constitutional principle of the protection of acquired rights and the general principles of administrative procedure. The permanence of the right acquired by the administrative decision is not absolute. Repeal or change of the administrative decision is possible only in the mode provided in the law, since the administrative decision makes use of the presumption of regularity. The deprivation of administrative and legal powers in the area of public law takes place in the context of an assessment of the implementation of an administrative decision carried out by a state body. This assessment is possible with the use of two procedural institutions for the expiry of an administrative decision and a substantive institution for the withdrawal of rights. The body assesses whether the addressee of an administrative act has implemented the administrative decision not only in accordance with its content but also the provisions of the generally applicable law. The deprivation of a party of an acquired right is often accompanied by the need to award damages (grant compensation). The procedure and premises for claiming compensation liability have been regulated in the provisions of substantive administrative law. The principle of the effectiveness of public administration bodies is one of the basic principles of administrative law. Its application is not limited only to the creation of law, but also includes the application of law by public administration bodies. The problem of the efficiency of operations of state bodies is of particular importance not only in the area of enforceability of an administrative decision, but also its authorising function. The efficiency of operations of entities in the State structure is assessed through the prism of the implementation of a given administrative decision.